Penyelesaian Perkara Pidana Terhadap Anak Melalui Diversi(Studi Kasus Wilayah Hukum Sukoharjo) - Rachma, Widi Famaliya, Dr. Natangsa Surbakti, S.H., M.Hum (2017)
This study aims to determine the completion of criminal cases against children through diversion and to determine what factors are becoming obstacles in solving criminal cases against children through a diversion of the offenses against children in the jurisdiction of Sukoharjo. The research method used juridical empirical method descriptive research sites in Sukoharjo Police Resort and residence of the RT a criminal offense occurred. The data source consists of primary data is the result of interviews and secondary data, legal data primary, secondary and tertiary. Data were collected by literature study and field studies (interviews) and analyzed qualitatively through deductive thinking. The results showed that the completion of criminal cases against children through diversion has been done at the level of investigation, most successful and have failed so delegated to the level of prosecution and to the court level with an end through the criminal justice system, while factors that are barriers to the completion of the diversion that the perpetrator does not confess or kink in providing information and the level of investigation is not their child's special investigator, facility dedicated space for mediation and temporary placement of a child is not yet available in the jurisdiction of Sukoharjo. Keywords: handling the case, juvenile justice, diversion